The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.1021/bi00680a008
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic model of the protein-mediated phosphatidylcholine exchange between single bilayer liposomes

Abstract: The phosphatidylcholine exchange protein from beef liver catalyzes the exchange of phosphatidylcholine between single bilayer liposomes (Hellings et al. (1974), Eur. J. Biochem. 47, 601). A model has been proposed which describes the kinetics of this exchange. Steady-state equations have been derived from the model and have been used for the derivation of the theoretical rate equation. Computer analysis shows a good fit with the experimental results. It follows from the analysis that the apparent dissociation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
44
0

Year Published

1976
1976
1985
1985

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(49 citation statements)
references
References 30 publications
5
44
0
Order By: Relevance
“…Previously in studying the transfer of phosphatidylcholine between single bilayer liposomes, it was demonstrated that the transfer decreased with an increase of negatively charged phosphatidic acid in the liposomes [2,3]. An analysis of the kinetic data indicated that the apparent dissociation constant of the exchange protein-liposome complex decreased in a parallel fashion resulting in an inhibition of transfer [3]. In the present study it has been confirmed that the incorporation of phosphatidic acid into phosphatidylcholine liposomes inhibits transfer (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Previously in studying the transfer of phosphatidylcholine between single bilayer liposomes, it was demonstrated that the transfer decreased with an increase of negatively charged phosphatidic acid in the liposomes [2,3]. An analysis of the kinetic data indicated that the apparent dissociation constant of the exchange protein-liposome complex decreased in a parallel fashion resulting in an inhibition of transfer [3]. In the present study it has been confirmed that the incorporation of phosphatidic acid into phosphatidylcholine liposomes inhibits transfer (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…It is presumably by this mechanism that in the present study the protein transfers ['4C]phosphatidylcholine from the 14C-labelled mitochondria to the liposomes. Previously in studying the transfer of phosphatidylcholine between single bilayer liposomes, it was demonstrated that the transfer decreased with an increase of negatively charged phosphatidic acid in the liposomes [2,3]. An analysis of the kinetic data indicated that the apparent dissociation constant of the exchange protein-liposome complex decreased in a parallel fashion resulting in an inhibition of transfer [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…-Val-Val-Tyr-Trp-Gln-Val-(positions 98 -104) and -Tyr-Val-Tyr-Val-(positions 114-117). At present, studies are in progress to establish how the endogenous binding site relates to the membrane interface when the protein forms a 'collision' complex with that interface [14].…”
Section: Discussionmentioning
confidence: 99%